Analisis Faktor-Faktor yang Mempengaruhi Tax Avoidance - Eva Nurul Ramdiani; Tri Gunarsih; Etty Puji Lestari (Politeknik Ganesha Medan, 2023)
Tax avoidance is one of the main issues that need to be followed up more seriously by various parties, especially the government, so it becomes an important issue to be investigated. This study aims to determine the effect of institutional ownership, corporate social responsibility, profitability, and capital intensity on tax avoidance. In addition, this study investigates whether audit quality moderates the effect of institutional ownership on tax avoidance. The tax avoidance variable in this study is proxied by using the Cash Effective Tax Rate (CETR). The population of this study is consumer cyclical companies listed on the Indonesia Stock Exchange in 2018 – 2020, with a total sample of 66 company data that meet the criteria. The data collection method used is the purposive sampling method. The primary analytical tool in this research is panel data regression analysis. The results showed that institutional ownership, profitability, and capital intensity had no significant effect on tax avoidance. In contrast, CSR has a negative and significant effect on tax avoidance. Audit quality does not moderate effect of institutional ownership on tax avoidance. Audit quality which acts as a form of transparent supervision with accurate disclosure is not a tool that can influence tax avoidance actions.